PERSEPSI WAJIB PAJAK ORANG PRIBADI MENGENAI DISKRIMINASI PAJAK, PENGETAHUAN PERPAJAKAN, DAN NORMA SUBJEKTIF TERHADAP ETIKA PENGGELAPAN PAJAK - Farah Nabilah (2020)
This research was conducted to examine and determine the perception of individual tax payers on tax discrimination, tax knowledge, and subjectif norm abaout the ethical of tax evasion. The independent variable used in this tax discrimination, tax knowledge, and subjectif norm. The population in this study was all individual taxpayers who are registered in KPP Pratama in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The sample in this study amounted to 100 individual taxpayers who are registered in KPP Pratama in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The data analysis technique used is Structural Equation Modeling (SEM) using the Partial Least Square application with a significance level of 5%. The results of this study indicate that tax discrimination has a significant effect on the ethical of tax evasion, whereas tax knowledge and subjective norm has no significant effect on the ethics of tax evasion.